PENGARUH PENGGUNAAN MULTIMEDIA FLIPBOOK TERHADAP KEMAMPUAN LITERASI SAINS SISWA KELAS 8 - Nining Anggreini; Andi Adam; Akram (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The use of learning media limited to blackboards and printed books can decrease student interest and participation. To address this, innovation with more interactive learning media is needed. Multimedia flipbooks are considered an alternative that can enhance student engagement and science literacy in the classroom. This study aims to assess the impact of using flipbooks on the science literacy of 8th-grade students at SMP Negeri 2 Sungguminasa, Gowa Regency. The research employs a quantitative method with a Pre-Experimental design, specifically a one-group pretest-posttest model. Data were analyzed using descriptive and inferential statistics with SPSS. The study involved 78 8th-grade students. Analysis results indicate that pretest and posttest data meet the normality test requirement (p ≥ 0.05), which is a prerequisite for hypothesis testing. The average science literacy scores are normally distributed. The analysis shows that the use of flipbooks has a positive and effective impact on improving students' science literacy, as evidenced by the t-value (72.449) being greater than the t-table value (1.664). The conclusion is that flipbooks positively influence the science literacy of 8th-grade students at SMP Negeri 2 Sungguminasa.